The Domestic Chicken as Legal Fiction: Cruelty for Profit - Crenshaw, Estée (Humanimalia, 2017)
This paper explores the legal fictions surrounding the domestic chicken and its place in animal agriculture through a comparison of law and cultural narrative. The legal fictions examined are that of chickens as already dead, chickens as things, and chickens as a collective. Through examination of these fictions, a narrative of cruelty arises that questions the current treatment of domestic chickens in animal agriculture.